1995
DOI: 10.1209/0295-5075/29/6/002
|View full text |Cite
|
Sign up to set email alerts
|

Electron Collision Cross-Sections Measured with the Use of a Magneto-Optical Trap

Abstract: PACS. 34.80i -Electron scattering. PACS. 32.80Pj -Optical cooling of atoms; trapping. PACS. 35.80 + s -Atomic and molecular measurement and techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
0
29
1
Order By: Relevance
“…In this technique, a laser is used to trap the atoms of interest, and absolute cross sections can be obtained directly from the trap loss when the laser is switched off. Examples of such measurements are the work of Schappe et al (1995) and MacAskill et al (2002). Lukomski et al (2006) showed that the technique can, in principle, also be used to obtain total cross sections from laser-excited initial states that would be hard to measure otherwise.…”
Section: Integral Cross Sectionsmentioning
confidence: 99%
“…In this technique, a laser is used to trap the atoms of interest, and absolute cross sections can be obtained directly from the trap loss when the laser is switched off. Examples of such measurements are the work of Schappe et al (1995) and MacAskill et al (2002). Lukomski et al (2006) showed that the technique can, in principle, also be used to obtain total cross sections from laser-excited initial states that would be hard to measure otherwise.…”
Section: Integral Cross Sectionsmentioning
confidence: 99%
“…This will be discussed in the results and discussion section. The technique used in our measurements is very similar to that adopted by Schappe et al [4]. The only difference being that they started with an empty trap and recorded the trap loading data, whereas we started with a fully loaded trap with steady-state number N 0 of Cs atoms and recorded the unloading data of the trap.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…These atoms can be easily excited using visible and NIR light sources and are, therefore, very convenient to study electron collisions with excited atomic states, as reported by Zuo et al [3]. Schappe et al [4] reported absolute values for the total electron scattering cross section, in the range from 7 to 500 eV, using a cloud of Rb cold atoms in a MOT. The use of ultracold atoms is very advantageous in this type of measurement, because the total cross section reported here depends only on the electron flux in the electron beam and the relative change in the atomic density of the trapped atoms and not on the total number of atoms.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations